Análise da salubridade do meio urbano com base na utilização de índices ambientais: aplicação na bacia de drenagem XII da cidade do Natal-RN - Figueiredo, Lucia Mara (2011)
The growing accumulation of people in urban centers caused chronic problems of the cities to begin to take an increasingly unsustainable. Primarily related to lack of infrastructure coupled with sanitation and lack of investment in critical sectors such as health, education, housing and transportation, these problems start to deteriorate markedly the quality of life of city dwellers and put into test management policies of the spaces urbanized. To reverse this situation, shows is essential to the use of tools (highlighting this harvest rates and environmental indicators) that help in assessing the current conditions and may assist in predicting future scenarios. From the information listed above, now put the research seeks to present an index called ISBA Environmental (Sanitation Index) which looks at the four urban systems (water, sewer, solid waste and urban drainage) from the viewpoint of application in a geographical cutout specific - in this case the Drainage Basin XII, defined by the Plan of Urban Drainage Stormwater in the city of Natal, capital of Rio Grande do Norte. This index, together with analysis of other factors sought to trace the current conditions of the basin and thus, assist in proposing the best solutions. For the preparation of the index was applied a questionnaire with a sample of 384 (three hundred eighty-four) households that aimed to study two variables: access to services and satisfaction of the population in relation to these. The ISBA has shown that the system is the most deficient collection and disposal of effluents (ICE = 47.66%), followed by the drainage of rainwater (IDAP = 54.17%), water supply (AAI = 61, 36) and solid waste collection (IRS = 78.28). With the ISBA was possible to verify that the qualitative data shows whose subjectivity is evident (as is the case of user satisfaction) can be of great importance when an assessment, since we obtained the correlation coefficient between the variables "Access" and " Satisfaction "equal to 0.8234, showing a strong correlation between the existence / quality of service offered and the impressions of the population that receives them